Multilingual K-Pop Idols' Influence on Language Acquisition among Surakarta K-Popers - Putri, Bela Pramesthi; Sarosa, Teguh; Monic, Ayu; Yulian, Azarya (JALL (Journal of Applied Linguistics and Literacy), 2024)
The Korean pop (K-POP) phenomenon is currently raging among fans in various countries. K-pop idols, who are icons in the industry, often speak multiple languages other than their native language (such as English, Japanese, and Chinese) to promote their content to the rest of the world. This study aims to determine the influence of multilingualism among K-pop idols on foreign language acquisition for K-popers in Surakarta through the content they see. This study used a mixed-methods design. Data was collected through a questionnaire consisting of 10 questions for 59 respondents aged 16 to 24 years old living in Surakarta. In addition, the researcher also analyzed media content, such as music shows, awards speeches, and reality shows, and conducted a literature review, which searched and reviewed academic articles, research reports, and other sources related to the topic. The results show that the multilingualism of K-pop idols affects the language acquisition of Surakarta fans. When fans see idols with multilingual abilities, they tend to respond positively as they are more motivated to learn the various languages. This study provides insight into how the multilingualism of K-pop idols is not only a means of entertainment but also indirectly affects the language acquisition of Surakarta fans. The implications of this study can be used as a basis for the development of a more contextualized and engaging language learning approach based on K-pop fans' interests.